Proximity can induce diverse friendships: A large randomized classroom experiment - Julia Marie Rohrer; Tamás Keller; Felix Elwert (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2020)
Can outside interventions foster socio-culturally diverse friendships? We executed a large field experiment that randomized the seating charts of 182 primary-school classrooms (N=2,996 students) for the duration of one semester. We found that being seated next to each other increased the probability of a mutual friendship from 15% to 22% on average. Furthermore, induced proximity increased the latent propensity toward friendship equally for all students, regardless of students' dyadic similarity with respect to educational achievement, gender, and ethnicity. However, the probability of a manifest friendship increased more among similar than among dissimilar students. Our findings demonstrate that a scalable light-touch intervention can affect face-to-face networks and foster diverse friendships in groups that already know each other, but they also highlight that transgressing boundaries defined by ethnicity and gender remains an uphill battle.
Keywords: C93; I21; I24; J18; Z13; 330; Friendship formation; Social networks; Diversity; Homophily; Randomized field experiment; Deskmates